Full disclosure : the perils and promise of transparency - Fung, Archon, 1968-; Graham, Mary, 1944-; Weil, David, 1961- (Cambridge : Cambridge University Press, 2007)
Governments in recent decades have employed public disclosure strategies to reduce risks, improve public and private goods and services, and reduce injustice. In the United States, these targeted transparency policies include financial securities disclosures, nutritional labels, school report cards, automobile rollover rankings, and sexual offender registries. They constitute a light-handed approach to governance that empowers citizens. However, as Full Disclosure shows these policies are frequently ineffective or counterproductive. Based on a comparative analysis of eighteen major policies, the authors suggest that transparency policies often produce information that is incomplete, incomprehensible, or irrelevant to the consumers, investors, workers, and community residents who could benefit from them. Sometimes transparency fails because those who are threatened by it form political coalitions to limit or distort information. To be successful, transparency policies must place the needs of ordinary citizens at centre stage and produce information that informs their everyday choices.
1. Governance by transparency -- The new power of information -- Transparency informs choice -- Transparency as missed opportunity -- A real-time experiment -- Transparency success and failure -- How the book is organized -- 2. An unlikely policy innovation -- An unplanned invention -- The struggle toward openness -- Why disclosure? -- 3. Designing transparency policies -- Improving on-the-job safety : one goal, many methods -- Disclosure to create incentives for change -- What targeted transparency policies have in common -- Standards, market incentives, or targeted transparency? -- 4. What makes transparency work? -- A complex chain reaction -- New information embedded in user decisions -- New information embedded in discloser decisions -- Obstacles : preferences, biases, and games -- How do transparency policies measure up? -- Crafting effective transparency policies -- 5. What makes transparency sustainable? -- Crisis drives financial disclosure improvements -- Sustainable policies -- The politics of disclosure -- Humble beginnings : prospects for sustainable transparency -- Two illustrations -- Shifting conditions drive changes in sustainability -- 6. International transparency -- How do international transparency policies work? -- Why now? -- From private committee to public mandate : international corporate financial reporting -- Improving a moribund system : international disease reporting -- The limits of international transparency : labeling genetically modified foods -- 7. Toward collaborative transparency -- Innovation at the edge -- Technology expands capacities of users, disclosers, and government -- Four emerging policies -- Challenges to collaborative transparency -- New roles for users, disclosers, and government -- Looking ahead : complementary generations of transparency -- 8. Targeted transparency in the information age -- Two possible futures -- When transparency won't work -- Crafting effective policies -- The road ahead -- Appendix : eighteen major cases -- Targeted transparency in the United States -- Targeted transparency in the international context.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Government information -- Access control -- United States; Transparency in government -- United States; Disclosure of information -- Government policy -- United States; Disclosure of information -- Law and legislation